Correlation of melatonin and TNF-α levels with characteristics of sleep in patients with rheumatoid arthritis - Yu. K. Sikalo; M. A. Stanislavchuk (Zaporožskij Medicinskij Žurnal)
Specific immune and neuroendocrine factors are considered in the pathogenic mechanisms of sleep disorders in RA.